Reinterpreting the Philosophy of Mahr in Islamic Family Law: A Maqāṣid al-Sharīʿah Analysis of Women's Economic Protection within the Banjar Jujuran Tradition - Yulianti; Amnah Abdullah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
In classical fiqh discourse, mahr is often situated within the framework of the muʿāwaḍah (exchange) contract, which, epistemologically, tends to reduce women's human value to legal objects. In the era of economic disruption, interpreting mahr as merely an administrative formality or a religious symbol undermines its protective function against a wife's economic vulnerability. This study aims to conduct a philosophical reinterpretation of mahr by shifting the paradigm from the mere symbolism of istimtāʿ toward the sovereignty of absolute milkiyyah (ownership) for women. This study is normative legal research employing statutory, conceptual, and comparative approaches. The analysis is conducted using the Maqāṣid al-Sharīʿah framework to examine the dimensions of the benefits of mahr within the structure of Indonesian family law. The findings reveal that mahr should be recontextualised as a ḍarūriyyāt (necessity) instrument functioning as a social safety net for women. The reinterpretation of mahr through the principles of ḥifẓ al-māl (protection of property) and ḥifẓ al-nafs (protection of life) requires its functionalization as productive assets with sustainable value. In the Indonesian context, particularly in regions where the jujuran tradition entails high marriage costs, there is a need to shift financial allocations from ceremonial expenditures toward strengthening sovereign mahr. In conclusion, this reinterpretation reinforces financial responsibility (qawwāmah) based on justice while offering a solution to women's economic vulnerability within the contemporary family law framework.